Islamic religiosity and Islamic financial asset holdings (IFAH). Issue 4 (8th July 2019) - Zainudin, Rozaimah; Mahdzan, Nurul Shahnaz; Che Hashim, Rosmawani; Sulaiman, Noor Adwa
Abstract : Purpose: This paper aims to examine the relationship between Islamic religiosity and Islamic financial asset holdings (IFAH) among Muslim individuals in Malaysia. Design/methodology/approach: Data for this study were collected through a survey questionnaire, and a sample of 751 working Muslims in Kuala Lumpur was obtained. Islamic religiosity was measured via religiosity levels and religiosity dimensions. IFAH was measured as the fraction of Islamic financial assets held in a financial portfolio. A generalized linear model (GLM) was used to estimate the relationships. Findings: The results show that religiosity level influences the IFAH. Devout Muslims held more Islamic financial assets than casual Muslims. All religiosity dimensions influenced IFAH, with faith having the greatest influence and virtues the least. Educational level strongly influenced IFAH. Research limitations/implications: The sample consisted of working Muslims in Kuala Lumpur; hence, generalization cannot be made to all Malaysian Muslims. This study only focused on Islamic financial assets and did not consider other types of Islamic financial products, such as financing. Practical implications: Efforts to encourage Muslims to opt for Islamic financial assets may be more effective if they begin from the core of religious education. Educating individuals on Islamic principles, including the values and concepts of Islamic finance, is important to encourage the Islamic banking industry to prosper among Muslims. Originality/value: The paper provides an extension of current literature on spirituality and religion by incorporating a comprehensive measure of Islamic religiosity and its relationship with financial asset holdings.